Commitment in the Household: Evidence from the Effect of Inheritances on the Labor Supply of Older Married Couples - David M. Blau; Ryan Goodstein (Institute for the Study of Labor (IZA), 2016)
We study the effect of receiving an inheritance on the labor force participation (LFP) of both the recipient and the recipient's spouse in a population of older married couples. An inheritance is not subject to laws governing division of marital property at divorce, because it is not acquired with income earned during marriage. Hence it plays the role of a "distribution factor" in the intrahousehold allocation of resources, increasing bargaining power of the recipient. Controlling for inheritance expectations, we interpret the receipt of an inheritance as a shock to wealth. Our results indicate that receiving an inheritance reduces LFP of the recipient by four percentage points, comparable in magnitude to the effect of a decline in health. However, an inheritance has little or no effect on LFP of the spouse. These estimates are inconsistent with a dynamic, collective model of the household in which spouses have the ability to commit to an ex ante efficient allocation. The results are consistent with a model of limited commitment in which a shock to household resources can alter bargaining power. We discuss the implications for reform of Social Security spouse and survivor benefits.
Keywords: J22; J26; 330; inheritances; commitment; labor force participation; retirement; collective model of household